The Application of Cooperative Learning Model Type Review Course Hooray (CRH) and Jigsaw Towards Students’ Learning Outcomes on Class X SMA Negeri 9 Palu in Redox Materials - Suheria, Suheria; Mustapa, Kasmudin; Said, Irwan (Jurnal Akademika Kimia, 2019)
A research on the application of cooperative learning model type course review hooray and jigsaw to the students’ learning outcomes of class X SMA Negeri 9 Palu on redox material has been implemented. This type of research was quasi-experiment with non-randomized pretest-posttest control group design. Determination of sample was done by purposive sampling method. The sample of this research was a student of class XA class as a control group (n =23) and student of class XB as experiment group (n=23). Data processing of students’ learning outcomes used a non-parametric test analysis Mann-Whitney U-Test test. The results showed that the mean of experiment class was bigger than control class that was 27.57>19.47. The statistical analysis resulted in sig. 2-tailed (0.033)˂0.05 and Zcount (-2.136)˂Ztable (-1.96). The influence of the application of cooperative learning model of course review hooray to students’ learning outcomes can also be seen in the descriptive statistic analysis with 2 mean posttest score for the experimental class was 69.60 while in control class was 59.39. The minimum criterion value was 68. Therefore, it can be concluded that there is an influence of application of cooperative learning model of course review horay type to the students’ learning outcomes of class X SMA Negeri 9 Palu in redox material.